2018
DOI: 10.1007/s12098-017-2591-y
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Prognostic Prediction Model to Determine Severe Dengue in Children

Abstract: Among seven WHO warning signs, predictors of severe dengue as suggested by the present multivariable prediction model include clinical fluid accumulation, persistent vomiting and hematocrit ≥0.40 concurrent with platelet count <100 × 10/L.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 22 publications
2
12
0
Order By: Relevance
“…13 A recent pediatric series from our institution found clinical fluid accumulation, persistent vomiting and hematocrit ≥0.40 concurrent with platelet count <100 × 109/L prognosticative of severe dengue. 14 Wahid in his series matched our observation that an elevated ALT was predictive of DHF. 15 Lee observed that, an elevated ALT was seen in severe dengue fever but could not predict DHF or severe dengue.…”
Section: Discussionsupporting
confidence: 80%
“…13 A recent pediatric series from our institution found clinical fluid accumulation, persistent vomiting and hematocrit ≥0.40 concurrent with platelet count <100 × 109/L prognosticative of severe dengue. 14 Wahid in his series matched our observation that an elevated ALT was predictive of DHF. 15 Lee observed that, an elevated ALT was seen in severe dengue fever but could not predict DHF or severe dengue.…”
Section: Discussionsupporting
confidence: 80%
“…The definition of vomiting was not given in most of the included studies, although two of eight studies defined vomiting as at least two episodes during the febrile phase of the illness. 25,26 For vomiting, a significant association was found in both pooled analyses (crude and adjusted estimates; figure 4; appendix p 43), and neither heterogeneity nor publication bias was found. Abdominal pain and tenderness were also consistently associated with progression to severe disease (OR 1•92 [95% CI 1•35-2•74]), although the definition was not given in all included studies and high heterogeneity was found (I²≥75%).…”
Section: Resultsmentioning
confidence: 94%
“…For clinical fluid accumulation (either pleural effusion or ascites detectable during the first 4 days of illness), four studies were included; three referred to both ascites and pleural effusion 25,26,29 and one referred to pleural effusion only. 30 Despite the small number of studies included in this analysis and little information on the method used for detecting effusion, we found a significant association between clinical fluid accumulation during the first 4 days of illness and progression to severe dengue, with low to moderate heterogeneity (I²=31%; figure 4).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We define lethargy as a state of energy insufficiency affecting Activities of Daily Living (ADL). Previous studies on prediction and prognostication of DF from signs and symptoms however did not show a significant relationship between lethargy and severe DF (Thein et al, 2013;Sreenivasan et al, 2018;Joshua et al, 2016).…”
Section: Discussionmentioning
confidence: 91%